Lymph nodal radiotherapy in breast cancer: what are the unresolved issues?. Issue 8 (3rd August 2021) - Fozza, Alessandra; Giaj-Levra, Niccolò; De Rose, Fiorenza; Ippolito, Edy; Silipigni, Sonia; Meduri, Bruno; Fiorentino, Alba; Gregucci, Fabiana; Marino, Lorenza; Di Grazia, Alfio; Cucciarelli, Francesca; Borghesi, Simona; et al.
ABSTRACT: Introduction : Sentinel lymph node biopsy (SLNB) is the gold standard in invasive breast cancer. Axillary dissection (ALND) is controversial in some presentations. Areas covered : Key questions were formulated and explored focused on four different scenarios in adjuvant axillary radiation management in early and locally advanced breast cancer. Answers to these questions were searched in MEDLINE, PubMed from June 1946 to August 2020. Clinical trials, retrospective studies, international guidelines, meta-analysis, and reviews were explored. Expert opinion : Analysis according to biological disease characteristics is necessary to establish the impact of ALND avoidance in unexpectedly positive SLNB (pN1) in cN0 patients. A low-risk probability of axillary recurrence was observed if axillary radiotherapy (ART) or ALND were offered without impact on outcomes. Adjuvant RNI in pT1-3 pN1 treated with mastectomy or BCS should be proposed in unfavorable disease and risk factors. In ycN0 after NACT, SLNB can be offered in selected cases or ALND should be performed. After SLNB post-NACT (ypN1), ALND and adjuvant radiotherapy are mandatory.